ANALYSIS OF CALCULATION AND ACCOUNTING OF INCOME TAX ACCOUNTING ARTICLE 21 FOR CIVILIANS EMPLOYEES'S STAFF IN THE REGIONAL OFFICE OF SIMALUNGUN DISTRICT - Januri Januri, S.E., M.M., M.Si (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA)
The purpose of this study is to know and analyze how the calculation of income tax article 21 on salaries of civil servants in The Land Office of Simalungun Regency for this and is in accordance with applicable tax laws.